2012
DOI: 10.1016/j.physa.2012.01.023
|View full text |Cite
|
Sign up to set email alerts
|

On the scaling of the distribution of daily price fluctuations in the Mexican financial market index

Abstract: In this paper, a statistical analysis of log-return fluctuations of the IPC, the Mexican Stock Market Index is presented. A sample of daily data covering the period from 04/09/2000 − 04/09/2010 was analyzed, and fitted to different distributions. Tests of the goodness of fit were performed in order to quantitatively asses the quality of the estimation. Special attention was paid to the impact of the size of the sample on the estimated decay of the distributions tail. In this study a forceful rejection of norma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 27 publications
(46 reference statements)
1
13
0
Order By: Relevance
“…Further, for this index the Lévy-stable law provides a much better fit than the NIG distribution [12]. Similar results have been observed for the IPC mexican index: the hypothesis of stability could not be rejected at 5% confidence level while the hypothesis of NIG distributed daily log-returns was clearly rejected [2]. However, according to our findings, the Lévy-stable model is not the best option for modeling the high-frequency returns of the Ibex35 since the NIG distribution is a much better candidate.…”
Section: Discussionsupporting
confidence: 79%
“…Further, for this index the Lévy-stable law provides a much better fit than the NIG distribution [12]. Similar results have been observed for the IPC mexican index: the hypothesis of stability could not be rejected at 5% confidence level while the hypothesis of NIG distributed daily log-returns was clearly rejected [2]. However, according to our findings, the Lévy-stable model is not the best option for modeling the high-frequency returns of the Ibex35 since the NIG distribution is a much better candidate.…”
Section: Discussionsupporting
confidence: 79%
“…This began with the work of Mandelbrot in 1963 [16], who showed that returns of cotton prices are more accurately modelled by an α-stable density with α = 1.7 than with a normal density, followed by the work of Fama in 1965 [8] arriving at a similar conclusion for daily returns of the Dow Jones Industrial Average. More recent investigations include α-stable behavior in Mexican financial markets [1], as well as financial modeling by more general Lévy processes [17,9]. The implications of heavy tailed behavior in financial processes cannot be underestimated in practice; Wilmott [39] gives the following example based on daily data of the S&P 500 from 1980-2004.…”
Section: Fractional Diffusion For Relative Stock Performance Many Tymentioning
confidence: 99%
“…The same is true for the multidimensional kernels G + and M + ν by linearity of the Fourier transform, and for G × and M × ν by Fubini's theorem. 1 In the machine learning literature, authors such as [31] describe this Fourier transform as the spectral density in the context of Bochner's theorem on stationary kernels, and write it in the equivalent form, up to Fourier transform convention:…”
mentioning
confidence: 99%
“…. , 100 and (σ x , σ y ) = (1, 1), (1, 2), (1,5), (2, 2), (2, 5), (5,5). For the bootstrap confidence interval, we took B = 500, as in Section 4.…”
Section: Simulation Study For Interval Estimators Of Rmentioning
confidence: 99%
“…According to O'Reilly and Rueda [28], times in supermarket sales, edge turbulence of fusion devices, network traffic behavior in switched Ethernet systems, modeling individual behavior in a large marine predator, evolutionary programming using mutations, distribution of marks in high school, fractal structures, models for fish locomotion, distribution of economical indices, south Spain seismic series, geophysical data analysis, supermarket sales, velocity difference in systems of vortex elements, currency exchange market, random field models for geological heterogeneity, structural reorganization in rice piles, and wave scattering from self-affine surfaces. Three of the most recent applications relate to daily price fluctuations in the Mexican financial market index (Alfonso et al [1]), observations of anomalous diffusion (Sagi et al, 2012), and bistable systems (Srokowski [33]). …”
Section: Introductionmentioning
confidence: 99%